PROBLEMS AND PROSPECTS OF THE EUROPEAN REGIONAL ORDER - L. A. Dymova (Vestnik MGIMO-Universiteta)
For the last few decades, the system of international relations continues to change. One of the key components of the emerging international order is the European regional order, which currently goes through deep transformations associated with changes of the international system and structural reconstruction of the European communities. The formation of the European regional system is a complex international political process, which is based on various political, social, economic, cultural, historical and other factors. Since the end of the World war II the European Union constitutes a political and institutional basis of relations both between member states and with the rest of the world. However, today the European Union runs through a systemic crisis embodied by ongoing economic and financial downturn as well as a crisis of socio-political structures and models of governance that now threaten the existence of the Union itself. Institutional problems are aggravated against the background of crises in highly sensitive areas such as economy and security, as well as uncertainties in the external international environment. All these factors undermine the ability of the EU to play a decisive role in building a European regional order. The emphasis is shifting towards particular countries, with the greater potential in shaping the international agenda and giving an effective response to modern challenges and threats. Building a stable architecture of the European security system is one of the essential conditions of the European regional order, however contradicting approaches of the parties acknowledge that political and ideological barriers between the East and the West continue to exist. In the context of increasing security threats transatlantic partnership does not lose the relevance though the tough course of the US and its desire to reinforce its leadership in Europe often meets the extreme disapproval on the part of the Europeans. Russian factor also plays inevitably important role, since Russia culturally and historically, economically and institutionally, is inextricably linked with Europe and is an integral part of the European regional complex.